Exergy analysis of a refrigeration plant [microfilm] - Wan, Choong Meng (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2003